Isolation and purification of an enzyme hydrolyzing ochratoxin A from aspergillus niger - Abrunhosa, Luís (2007)
Ochratoxin A is a mycotoxin produced by several Aspergillus and some Penicillium species which may be present in food and feed products. It can be enzymatically hydrolyzed into ochratoxin α and l-β-phenylalanine, thereby decreasing its toxicity. The ochratoxin A degradation capacity of Aspergillus niger is well known and here we report the isolation and purification of a novel enzyme from A. niger that hydrolyzes this mycotoxin. A wheat germ medium supplemented with ochratoxin A was used to produce the enzyme, which was purified from culture filtrate by acetone precipitation and anion exchange chromatography. An overall purification of 2.5-fold with a recovery of 68% and a final specific activity of 36 U/mg was obtained. The enzyme is a metalloenzyme as it was inhibited at 10 mM EDTA, whereas PMSF had no effect. The ochratoxin A hydrolytic enzyme presented a V max of 0.44 μM/min and a K m of 0.5 mM when the reaction was carried out at pH 7.5 and 37°C.